Disturbance and strategies for reactivation of the circadian rhythm system in aging and Alzheimer’s disease - Wu, Ying-Hui; Swaab, Dick F. (Sleep medicine, 2007)
Circadian rhythm disturbances, such as sleep disorders, are frequently seen in aging and are even more pronounced in Alzheimer’s disease (AD). Alterations in the biological clock, the suprachiasmatic nucleus (SCN), and the pineal gland during aging and AD are considered to be the biological basis for these circadian rhythm disturbances. Recently, our group found that pineal melatonin secretion and pineal clock gene oscillation were disrupted in AD patients, and surprisingly even in non-demented controls with the earliest signs of AD neuropathology (neuropathological Braak stages I–II), in contrast to non-demented controls without AD neuropathology. Furthermore, a functional disruption of the SCN was observed from the earliest AD stages onwards, as shown by decreased vasopressin mRNA, a clock-controlled major output of the SCN. The observed functional disconnection between the SCN and the pineal from the earliest AD stage onwards seems to account for the pineal clock gene and melatonin changes and underlies circadian rhythm disturbances in AD. This paper further discusses potential therapeutic strategies for reactivation of the circadian timing system, including melatonin and bright light therapy. As the presence of melatonin MT1 receptor in the SCN is extremely decreased in late AD patients, supplementary melatonin in the late AD stages may not lead to clear effects on circadian rhythm disorders.